DEVELOPING SOFT SKILLS IN THE EDUCATIONAL PROCESS: METHODOLOGICAL APPROACHES - Fazlijanov , Ilshat; Mustafoyev , Akmal (Scientific practical conference, 2026)
In the context of rapid global changes and the growing demands of the labor market, the development of soft skills has become a critical objective of modern education systems. Soft skills such as communication, teamwork, problem-solving, and critical thinking are essential competencies that complement academic knowledge and enhance employability. This study examines methodological approaches to developing soft skills in the educational process. The research is based on theoretical analysis, comparative review, and synthesis of pedagogical practices. The findings indicate that interactive teaching methods, project-based learning, collaborative activities, and digital tools significantly contribute to the development of soft skills among students. The study proposes a comprehensive methodological framework for integrating soft skills into educational curricula. The results highlight the importance of aligning teaching strategies with labor market requirements and fostering a learner-centered educational environment.